Improvement of Metal-Doped β-TCP Scaffolds for Active Bone Substitutes via Ultra-Short Laser Structuring - Soares, Íris; Sotelo, Lamborghini; Erceg, Ina; Jean, Florian; Lasgorceix, Marie; Leriche, Anne; Sikirić, Maja Dutour; Marušić, Katarina; Christiansen, Silke; Daskalova, Albena (Bioengineering, 2023)
Various efforts have been made to develop antibacterial biomaterials capable of also sustaining bone remodulation to be used as bone substitutes and reduce patient infection rates and related costs. In this work, beta-tricalcium phosphate (β-TCP) was chosen due to its known biocompatibility and use as a bone substitute. Metal dopants were incorporated into the crystal structure of the β-TCP, and disks were produced from this material. Magnesium and strontium, as well as copper and silver, were chosen as dopants to improve the osteogenic and antibacterial properties, respectively. The surface of the β-TCP samples was further modified using a femtosecond laser system. Grid and line patterns were produced on the plates’ surface via laser ablation, creating grooves with depths lower than 20 μm and widths between 20 and 40 μm. Raman and FTIR analysis confirmed that laser ablation did not result in the degradation or phase change of the materials, making it suitable for surface patterning. Laser ablation resulted in increased hydrophilicity of the materials, as the control samples (non-ablated samples) have WCA values ranging from 70° to 93° and become, upon laser ablation, superwicking surfaces. Confocal measurements show an increase in specific surface area of 50% to 200% compared to the control. Overall, the results indicate the potential of laser ablation to improve the surface characteristics of β-TCP, which may lead to an improvement in the antibacterial and osteogenic properties of the produced materials.
CRIS-Team Scopus Importer:2024-12-16
Keywords: bone substitute; femtosecond laser; laser ablation; β-TCP